JURIDICAL ANALYSIS OF JUDGES’ CONSIDERATIONS IN COMPENSATION DECISIONS FOR COPYRIGHT INFRINGEMENT (STUDY OF DECISION NOMOR 92/PDT.SUS-HKI/HAK CIPTA/2024/PN NIAGA JKT.PST - Sherla Demelan Tamara; Any Nugroho; Elin Sudiarti (SOSIOEDUKASI, 2026)
The research focuses on the judge’s legal reasoning in the Central Jakarta Commercial Court ruling No. 92/Pdt.Sus-HKI/Hak Cipta/2024/PN Niaga Jkt.Pst regarding song copyright infringement. The purpose is to examine the basis of the judge's consideration in determining compensation and assess the accuracy of the legal basis used based on the principle of legal certainty. Normative juridical methods underpin this study, combining legislative, case, and conceptual approaches. The findings uncover that judges seek to safeguard the economic rights of creators; however, the legal foundation applied is not entirely appropriate, as it reflects a conflation of criminal and civil norms. In addition, the determination of compensation is not explained in detail and has not taken into account the royalty standards set by the LMKN. The study shed light that the decision reflects an inconsistency in the application of copyright law by combining civil and criminal legal norms in determining compensation, thereby weakening legal certainty and creating ambiguity in the legal basis for resolving song copyright infringement disputes.